2018
DOI: 10.21614/chirurgia.113.5.593
|View full text |Cite
|
Sign up to set email alerts
|

Acute Abdomen in Diabetic Patients - What Should We Do?

Abstract: Diabetul zaharat este o afecţiune metabolică bine cunoscută, a cărei incidenţă este în creştere în întreaga lume. Particularităţile anatomo-patologice şi clinice ale multor afecţiuni, inclusiv ale abdomenului acut, sunt modificate semnificativ la pacienţii diabetici, ceea ce impune o strategie terapeutică nuanţată. În principal, două atitudini pot fi eronate, ambele cu efect negativ asupra evoluţiei pacienţilor: o intervenţie chirurgicală întârziată în cazul unei peritonite, datorită aspectului său clinic şi b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In 19 of the analyzed articles, diabetes was discussed as an independent risk factor for acute cholecystitis and in 14 of them diabetes was confirmed as an independent risk factor for developing this disease [1, [8][9][10][11][12][13][14][15][16][17][18][19]. Two studies analyzed this correlation in detail and in one it was significant only for women (p < 0,001), while in another it was significant only for men (p < 0,001) [20][21]. On the contrary, in 3 studies diabetes was not confirmed as an independent risk factor for acute cholecystitis [22][23][24].…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 19 of the analyzed articles, diabetes was discussed as an independent risk factor for acute cholecystitis and in 14 of them diabetes was confirmed as an independent risk factor for developing this disease [1, [8][9][10][11][12][13][14][15][16][17][18][19]. Two studies analyzed this correlation in detail and in one it was significant only for women (p < 0,001), while in another it was significant only for men (p < 0,001) [20][21]. On the contrary, in 3 studies diabetes was not confirmed as an independent risk factor for acute cholecystitis [22][23][24].…”
Section: Complicationsmentioning
confidence: 99%
“…Surgical site infection (SSI) in patients with diabetes has been discussed by the authors of 8 papers. In 6 articles it was reported that diabetes is a risk factor for SSI [13,[37][38][40][41][42]. In one paper diabetes did not affect significantly the incidence of SSI [33].…”
Section: Complicationsmentioning
confidence: 99%